Noninvasive neurological monitoring to enhance pLVAD-assisted ventricular tachycardia ablation – a Mini review - De Potter, Tom; Valeriano, Chiara; Buytaert, Dimitri; Bouchez, Stefaan; Ector, Joris (Frontiers in Cardiovascular Medicine, 2023)
For critically ill patients, hemodynamic fluctuations can be life-threatening; this is particularly true for patients experiencing cardiac comorbidities. Patients may suffer from problems with heart contractility and rate, vascular tone, and intravascular volume, resulting in hemodynamic instability. Unsurprisingly, hemodynamic support provides a crucial and specific benefit during percutaneous ablation of ventricular tachycardia (VT). Mapping, understanding, and treating the arrhythmia during sustained VT without hemodynamic support is often infeasible due to patient hemodynamic collapse. Substrate mapping in sinus rhythm can be successful for VT ablation, but there are limitations to this approach. Patients with nonischemic cardiomyopathy may present for ablation without exhibiting useful endocardial and/or epicardial substrate-based ablation targets, either due to diffuse extent or a lack of identifiable substrate. This leaves activation mapping during ongoing VT as the only viable diagnostic strategy. By enhancing cardiac output, percutaneous left ventricular assist devices (pLVAD) may facilitate conditions for mapping that would otherwise be incompatible with survival. However, the optimal mean arterial pressure to maintain end-organ perfusion in presence of nonpulsatile flow remains unknown. Near infrared oxygenation monitoring during pLVAD support provides assessment of critical end-organ perfusion during VT, enabling successful mapping and ablation with the continual assurance of adequate brain oxygenation. This focused review provides practical use case scenarios for such an approach, which aims to allow mapping and ablation of ongoing VT while drastically reducing the risk of ischemic brain injury.